2022
DOI: 10.1017/jfm.2022.659
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional density field of a screeching under-expanded jet in helical mode using multi-view digital holographic interferometry

Abstract: A synchronised multi-axis digital holographic interferometry set-up is presented for the study of 3-D flow fields with large density gradients. This optical configuration provides instantaneous interferograms with fine spatial resolution in six directions of projection. A regularised tomographic approach taking into account the presence of possible shock waves is furthermore considered to reconstruct 3-D density fields. Applied to a screeching under-expanded supersonic jet with helical dynamics, this set-up is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…The dominance of the mode in the results of Léon et al. (2022) provides at last this rigorous proof. Through the application of proper orthogonal decomposition, the authors then demonstrated that the helicity changes sign frequently during the continuous operation of the jet.…”
Section: Overviewmentioning
confidence: 65%
See 4 more Smart Citations
“…The dominance of the mode in the results of Léon et al. (2022) provides at last this rigorous proof. Through the application of proper orthogonal decomposition, the authors then demonstrated that the helicity changes sign frequently during the continuous operation of the jet.…”
Section: Overviewmentioning
confidence: 65%
“…Léon et al. (2022) combined an experimental set-up of significant complexity with elegant mathematical techniques to educe not only the time-averaged flow structures of such a jet, but also the three-dimensional structure of the leading azimuthal Fourier modes of the flow. The authors implemented a TDHI technique based on an arrangement of six Mach–Zehnder interferometers.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations